2012
DOI: 10.1016/j.phytochem.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and gene expression analysis in cold-acclimated guayule (Parthenium argentatum) rubber-producing tissue

Abstract: Natural rubber biosynthesis in guayule (Parthenium argentatum Gray) is associated with moderately cold night temperatures. To begin to dissect the molecular events triggered by cold temperatures that govern rubber synthesis induction in guayule, the transcriptome of bark tissue, where rubber is produced, was investigated. A total of 11,748 quality expressed sequence tags (ESTs) were obtained. The vast majority of ESTs encoded proteins that are similar to stress-related proteins, whereas those encoding rubber b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 75 publications
2
22
0
Order By: Relevance
“…We validated the expression of these genes from leaf and/or latex cDNA pools, detecting at least one isoform for the majority of the gene families (in Additional file 1: Table S16). We also made a comparison with the ESTs obtained from the rubber-producing bark tissue of guayule [31]. We found that 360 of the H. brasiliensis genes were represented in the guayule ESTs, of which 205 showed more than 70% sequence identity with the best match (in Additional file 2: Table S17).…”
Section: Resultsmentioning
confidence: 99%
“…We validated the expression of these genes from leaf and/or latex cDNA pools, detecting at least one isoform for the majority of the gene families (in Additional file 1: Table S16). We also made a comparison with the ESTs obtained from the rubber-producing bark tissue of guayule [31]. We found that 360 of the H. brasiliensis genes were represented in the guayule ESTs, of which 205 showed more than 70% sequence identity with the best match (in Additional file 2: Table S17).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we observed the premature induction of TbSRPP1–3 under cold stress, which is known to promote rubber biosynthesis in guayule and can also induce the laticifer‐specific HbSRPP promoter in T . brevicorniculatum , the latter also being activated by light and by rubber tapping (Cornish and Backhaus, ; Ponciano et al ., ; Tata et al ., ; Guo et al ., ). The proposed phylogenetic origin of TbSRPPs suggests they may be involved in stress responses, enabling them to promote rubber production under certain environmental conditions.…”
Section: Discussionmentioning
confidence: 98%
“…However, overexpression of HMGR only caused increased rubber yield in young P. argentatum plants under controlled environment; these increases were not maintained in field‐grown transgenics, although an interesting correlation of expression level and heat tolerance was observed (Dong et al ., ). Transcriptome analysis of cold‐acclimated P. argentatum ESTs (a total of 11 748) found that most of the ESTs were from genes encoding stress‐related proteins, while only just 1% of the ESTs were identified as rubber biosynthesis‐related (Ponciano et al ., ). Also, as in H. brasiliensis , a multigene family encodes the P. argentatum HMGS and HMGR (Ponciano et al ., ).…”
Section: Proteins and Genes Involved In Nr Substrate Biosynthesismentioning
confidence: 97%